Two new Gastroptychia Kobelt & Möllendorff, 1900 from Darjeeling and West Khasi Hills, northeastern India (Gastropoda: Cyclophoroidea: Diplommatinidae) - Chen, Zhe-Yu; Ablett, Jonathan D. (Zootaxa, 2024)
Two new species, namely Gastroptychia geoffreyi sp. nov. and Gastroptychia collicola sp. nov., are described respectively from Darjeeling and West Khasi Hills, northeastern India based on historical collections at the Natural History Museum, London. Gastroptychia collicola sp. nov. is distinguished from sympatric species by the presence of a unique palatal swelling and a palatal lamella, while Gastroptychia geoffreyi sp. nov. is distinguished from sympatric species by its dense ribs. The type specimens of all sympatric sinistral species, namely Gastroptychia insignis (Godwin-Austen, 1870), Gastroptychia gibbosa (W. T. Blanford, 1868), Gastroptychia gibberosa (Godwin-Austen, 1892), and Gastroptychia jaintiaca (Godwin-Austen, 1870), are illustrated for comparison.